2018
DOI: 10.1007/s00268-018-4514-0
|View full text |Cite
|
Sign up to set email alerts
|

Segmentectomy Versus Lobectomy for Radiologically Pure Solid Clinical T1a‐bN0M0 Lung Cancer

Abstract: Segmentectomy with intraoperative assessment of lymph node metastasis and adequate surgical margin may be a feasible surgical procedure for pure solid tumors in clinical T1a-bN0M0 lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…For overall survival, 6 studies [1620, 22] were eligible for inclusion in the analysis. The combined HR for these 6 studies was 1.52 (95% CI, 0.95–2.43; P = 0.08), and a fixed-effects model was applied (I 2 = 0%, P = 0.845), meaning that there was no significant difference between the segmentectomy and lobectomy groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For overall survival, 6 studies [1620, 22] were eligible for inclusion in the analysis. The combined HR for these 6 studies was 1.52 (95% CI, 0.95–2.43; P = 0.08), and a fixed-effects model was applied (I 2 = 0%, P = 0.845), meaning that there was no significant difference between the segmentectomy and lobectomy groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide, tumor size of 2 cm is considered the cutoff point in order to consider a sublobar resection. Several studies have shown that tumor size greater than 2 cm is an independent risk factor for recurrence in patients undergoing sublobar resections and the survival advantage or equivalence of sublobar resection is only demonstrated with tumors smaller than 2 cm (15). For these reasons, we do not indicate a segmentectomy as an intentional procedure in tumors >2 cm.…”
Section: Discussionmentioning
confidence: 73%
“…A recent study revealed that the oncology effect of anatomic segmentectomy and wedge resection were equivalent, but this study was limited to patients with peripheral lung carcinoma ≤ 20 mm in size who are clinically lymph node-negative ( 5 , 12 , 25 ). According to the study by Sihoe AD, predictors of successful preoperative CT sublobar resection include the following: location in the outer third of lung parenchyma; lesions <3 cm; and no evidence of endobronchial involvement ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…An intraoperative assessment of lymph node metastasis and an adequate surgical margin may be a viable surgical approach for pure solid tumors of clinical T1A-BN0M0 lung cancer, and patients who undergo segmental resection of tumors in the right upper lobe or basal segment have a higher rate of regional recurrence. Thus, it is necessary to perform these procedures carefully ( 25 ).…”
Section: Discussionmentioning
confidence: 99%